2016
DOI: 10.22146/jieb.10316
|View full text |Cite
|
Sign up to set email alerts
|

The Middle-Income Trap: Is There a Way Out for Asian Countries?

Abstract: This study aims at investigating the phenomena of the middle-income trap found in developing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Humans have different abilities and potentials, hence the need to develop their ability and potential. Research conducted by Salazar-Acosta (2006), Lubis and Saputra (2015), Abedullah and Mushtaq (2007) and Adojutelegan et al (2015) also obtained the results of research that labor has a positive and significant effect on production. Ng’ombe and Kalinda (2015), as well as research conducted by Ho et al (2014), stated that labor is the most influential factor in production.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Humans have different abilities and potentials, hence the need to develop their ability and potential. Research conducted by Salazar-Acosta (2006), Lubis and Saputra (2015), Abedullah and Mushtaq (2007) and Adojutelegan et al (2015) also obtained the results of research that labor has a positive and significant effect on production. Ng’ombe and Kalinda (2015), as well as research conducted by Ho et al (2014), stated that labor is the most influential factor in production.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Therefore a community must empower and invest resources for women to produce significant development impacts (Todaro & Smith, 2013). Lubis & Saputra (2015) argue that developing countries in Asia including Indonesia should maximize their main/key sectors, to takeadvantage of the resources at their disposal.Research which is conducted In Bangladesh, India, Indonesia, and South Africa, it was found that there are obstacles for women in entrepreneurship, namely; (1) Laws, customs, traditions, culture and religion (2) marital status (3) heavy housework (4) limited education, knowledge and information (5) limited funds as capital and access to credit (6) Ganesan, Kaur & Maheshwari, 2002;Sharma, 2013;Tambunan, 2008 ;Tambunan, 2009).These constraints lead to a tendency for women to choose business fields that do not require high skills and large capital, simple technology and easy to manage.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia has several challenges to achieving sustainable development. First, Indonesia has entered into the middle-income trap (Lubis & Saputra, 2016). Basri et al (2016) stated that the Indonesian economy has shown remarkable progress in the last four decades.…”
Section: Introductionmentioning
confidence: 99%
“…Second, there is a problem with a low-educated workforce. A country's per capita income can be improved by increasing government expenditure, investment spending, high technology exports, and human capital (Lubis & Saputra, 2016). Compared to most middleincome countries, Indonesia is left behind in building its human resource stock (Basri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%